On the performance of hybrid THz/FSO system - Sharma, Shubha (2024)
To establish a reliable and ultra-high-data-rate link, this letter presents a hybrid terahertz (THz)/free space optical (FSO) system, where the data is transmitted simultaneously over both the links and is combined at the destination using maximal ratio combining (MRC). The effect of path loss, pointing errors, and channel fading are considered for both THz and FSO links. Novel statistical characteristics are presented and the exact analytical and asymptotic expressions are obtained for the outage probability and average bit-error-rate (BER). Based on the asymptotic expressions, diversity order is obtained for the proposed system. The obtained diversity order is dependent on the atmospheric and channel fading parameters of both the links. Numerical results show that the hybrid THz/FSO system is highly reliable and exploits the complementary nature of both the links in various molecular attenuation and weather conditions.